Morphological Changes in Brast Neoplasia and Their Clinical Significance (Literature Review) - Beknazarov Kh. J.; Safarova Kh. Sh. (American Journal of Biomedicine and Pharmacy, 2026)
Breast neoplasia is one of the most common oncological diseases among women, and an in-depth study of its morphological characteristics is of great importance in determining diagnosis, prognosis, and treatment tactics. This literature review analyzes modern morphological changes observed in malignant and benign breast neoplasms, their histogenetic characteristics, and pathomorphological assessment criteria. In recent years, based on foreign and domestic sources, the histological types of tumors, degrees of differentiation, invasive characteristics, and the clinical significance of tumor microenvironment components have been highlighted. The diagnostic, prognostic, and predictive significance of biomarkers such as the estrogen receptor (ER), progesterone receptor (PR), HER2/neu, and Ki-67, which are widely used in immunohistochemical studies, was also evaluated. It has been shown that the integration of morphological and molecular-pathological data makes it possible to determine the biological behavior of breast cancer, assess the course of the disease and the risk of metastasis, and choose a personalized treatment strategy. An analysis of the literature showed that in modern pathomorphology, morphological diagnosis has become not only a diagnostic method but also an important prognostic and therapeutic tool for managing oncological patients.